Directional transport and coalescence behavior on Titanium-Tantalum alloy surface: Insights from experiment and molecular dynamics simulation. (February 2023) - Liu, Chenhua; Zhu, Xijing; Ye, Linzheng; Tong, Zhe; Li, Xiangmeng
Abstract: Friction and wear of artificial joints are severe problems. By designing a structure for directional transporting lubricant onto the Ti-Ta alloy surface, the friction or wear can be effectively reduced. Herein, molecular dynamics (MD) simulation and experiment were employed to study the directional transport and coalescence behavior of droplets on wedge-shape structure Ti-5Ta (wt%) alloy surface. Results show that water droplets can be continuously transported. Moreover, the experimental results of static and dynamic contact angle measurement show that the experiment agrees well with the MD simulation. Finally, the anti-gravity directional transport was achieved on a tilting Ti-5Ta (wt%) alloy surface. This work provides insights for reducing friction and extending service life of artificial joints in the medical field. Graphical Abstract: ga1 Highlights: Lennard-Jones potential was adopted to verify the surface wetting properties of Ti-Ta alloy. Directional transport and coalescence of nano-droplets was achieved on crossing wedge-shape structure of Ti-Ta alloy. Anti-gravity directional transport of droplets was achieved on the tilting surfaces of Ti-5Ta (wt%) alloy.